Modelling of Heat Loss in Closed Vessels during propellant Burning - KulKarni, U.P.; Naik, Smita D. (Defence Science Journal, 2013)
Closed vessel technique is essentially used to determine the force constant, vivacity and the burning rate of gun propellants. In fact, it is the only method to find out these three parameters experimentally. It is a well-known fact that however small the propellant burning time may be, there will be heat loss to the walls of the vessel due to conduction, convection, radiation and also due to the expansion of the vessel. This fact necessitates applying correction to the observed maximum pressure in the experiment. An analysis is presented in this paper as to how this heat loss can be modelled along with discussion about other models reported in this field.